Fur, fortune, and empire [compact disc, unabridged] : the epic history of the fur trade in America - Dolin, Eric Jay (Blackstone Audio, 2010)
Chronicles the colorful history of the American fur trade. Starting in the 1600s, the fur trade became the basis for the American economy. Communities depended on fur trappers for trading food and materials. However, the fur trade was not without its dark side as a number of Native American tribes and the animal population were irreparably damaged by the demand for fur.